The role of expatriates in MNCs knowledge mobilization - Mariano, Stefania; Mohamed, Mirghani; Mohiuddin, Qadir; Ghauri, Pervez N., 1948- (Bingley, U.K. : Emerald, 2011)
This book explores the role of expatriates in the mobilization and nurturing of knowledge between their original (parent/home) country and the MNCs host countries. This includes the management of knowledge and the tools, methods and practices that can be customized to facilitate the transfer of knowledge in MNCs settings. The text is an in-depth international compendium of theoretical and empirical studies about the role of expatriates in knowledge transfer at global levels. Thorough and comprehensive, it covers topics recognized by practitioners, academics, and researchers, yet about which very little has been published at an international level. Coverage includes: organizational culture; cross-cultural differences; globalization; cross-generational issues, technology-based sharing systems; intellectual capital management; linguistic differences; and distinctive political practices. It investigates the challenges imposed by culture, generation, tools, laws, regulations, and language, and examines the benefits of knowledge management principles that originate from different cultures, heterogeneous knowledge, and diverse intellectual capital management in global settings.
ch. 1. Theoretical perspectives on expatriate gender diversity / Susan Shortland -- ch. 2. The inherent challenges of knowledge transfer across countries and cultures / Tracy Stanley, Paul Davidson -- ch. 3. Knowledge flows in international business : A JIBS / Orly Yehezkel, Oded Shenkar -- ch. 4. Expatriate perspectives on knowledge transfers into Central and Eastern Europe / Adam Smale, Vesa Suutari -- ch. 5. Can a new measure of'managerial' knowledge be a good predictor of managerial ability in Mexico's maquiladora / JosCastillo, Debra Cartwright, Harold Harlow -- ch. 6. Integrating repatriated managers in MNCs / Avan Jassawalla, Hemant C. Sashittal -- ch. 7. U.S. expatriates, postwar knowledge transfer and Japanese telecommunications revival / Stephen B. Adams, Paul J. Miranti -- ch. 8. Organisational learning from Chinese returners : an exploratory study of the role of cross-cultural interactions / Ariane Berthoin Antal, Eva-Maria Walker -- ch. 9. Living and working between two worlds : using qualitative phenomenological findings to enhance understanding of lived experiences / Roger C. Russell, Catherine E. Aquino-Russell -- ch. 10. Training day : intercultural communication training for expatriates : the quest to improve intercultural communication competence / Bernd Kupka -- ch. 11. Preparing expatriate managers of multinational organisations for the cultural and learning imperatives of their job in dynamic knowledge-based environments / Ted O'Keeffe.
Keywords: International business enterprises; Foreign workers